Untargeted Screening of Per- and Polyfluoroalkyl Substances (PFASs) in Airborne Particulate of Three Italian E-Waste Recycling Facilities - Carolina Barola; Elisabetta Bucaletti; Simone Moretti; Francesca Buiarelli; Giulia Simonetti; Franco Lucarelli; Laura Goracci; Stefano Lorenzetti; Patrizia Di Filippo; Donatella Pomata; Carmela Riccardi; Roberta Galarini (Separations, 2023)
Poly- and perfluorinated alkyl substances (PFASs) are widely used in the electrical and electronic appliance industry to the point that waste of electrical and electronic equipment (WEEE), also known as e-waste, creates significant potential for PFAS exposure (by inhalation, ingestion, or dermal exposure) for people handling and recycling e-waste. The aim of this work was the development of an untargeted analytical approach in order to detect the presence of possible unknown PFASs in particulate matter collected in three Italian e-waste facilities through liquid chromatography coupled to high-resolution tandem mass spectrometry (LC-HR-MS/MS) in negative ionization mode. By means of three acquisition experiments, nine compounds were detected as candidate PFASs, and three were definitively confirmed by comparison with their authentic standards. Among these, bistriflimide (bis (trifluoromethylsulfonyl) imide), an ionic liquid with several promising technological applications, was the most abundant compound detected in all three recycling plants. This is the first study associating the presence of fluorinated ionic liquids with e-waste, and as these chemicals are not only toxic and persistent but also highly mobile, our results indicate the need to include them in future PFAS research. Only further data on their actual environmental diffusion will determine whether they are emerging pollutants or not.